2011
DOI: 10.1021/jf103591p
|View full text |Cite
|
Sign up to set email alerts
|

Improving Laccase Catalyzed Cross-Linking of Whey Protein Isolate and Their Application as Emulsifiers

Abstract: Whey protein isolate (WPI) was chemically modified by vanillic acid in order to enhance its cross-linkability by laccase enzyme. Incorporation of methoxyphenol groups created reactive sites for laccase on the surface of the protein and improved the efficiency of cross-linking. The vanillic acid modified WPI (Van-WPI) was characterized using MALDI-TOF mass spectrometry, and the laccase-catalyzed cross-linking of Van-WPI was studied. Furthermore, the vanillic acid modification was compared with the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 36 publications
(67 reference statements)
3
36
0
2
Order By: Relevance
“…As observed in this work, emulsion composed of protein (vanillic acid modified WPI) and laccase also showed polydisperse droplet size distribution with some secondary peaks and a slight increase in mean droplet size when compared to emulsions stabilized only by protein (Ma et al, 2011). The increase in mean droplet size could be associated to the formation of a thicker interfacial layer due to modifications in caseinate structure caused by cross-linking of protein onto interface (Chen et al, 2010).…”
Section: Microstructure and Droplet Size Distributionsupporting
confidence: 51%
See 2 more Smart Citations
“…As observed in this work, emulsion composed of protein (vanillic acid modified WPI) and laccase also showed polydisperse droplet size distribution with some secondary peaks and a slight increase in mean droplet size when compared to emulsions stabilized only by protein (Ma et al, 2011). The increase in mean droplet size could be associated to the formation of a thicker interfacial layer due to modifications in caseinate structure caused by cross-linking of protein onto interface (Chen et al, 2010).…”
Section: Microstructure and Droplet Size Distributionsupporting
confidence: 51%
“…Ferulic acid is a small molecule that can easily interact with the laccase or protein substract, improving cross-linking. Ferulic acid can transfer electrons to protein, which can be bounded by radical or directly bounded between two residues of tyrosine of protein (Ma et al, 2011). According to Steffensen et al (2008), α s -casein was not fragmented or covalently bonded when treated only with laccase, while the addition of ferulic acid leads to aggregates formation with molecular weight higher than 206 kDa.…”
Section: Polyacrylamide Gel Electrophoresis (Sds-page)mentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, studies have also shown that laccase can cross-link whey protein isolate (WPI) in the presence of phenolic acids (Ma, Forssell, Partanen, Buchert, & Boer, 2011). It is therefore possible that the laccase used in our experiments may initiate WPIeWPI cross-linkings, beet pectinebeet pectin cross-linkings, and/or WPIebeet pectin cross-linkings between pre-formed complex coacervations.…”
Section: Introductionmentioning
confidence: 97%
“…Whey proteins have been polymerized with different origin laccases in the presence of chlorogenic acid (Faergemand et al, 1998), ferulic acid (Steffensen et al, 2008), vanilic acid (Ma et al, 2011), and apple or cherry phenolics (Tantoush et al, 2011). Similarly, caseins have also been cross-linked either in the presence or absence of phenolic mediators (Ercili Cura et al, 2009;Hiller and Lorenzen, 2009;Paananen et al, 2013;Selinheimo et al, 2008;Stanic et al, 2010;Steffensen et al, 2008).…”
Section: Laccasementioning
confidence: 99%